Evaluación de biodigestores plásticos utilizando dos tipos de sustratos. - Zelaya Corea, Estela Marina; Somarriba Olivas, Enrique Javier; Beteta Herrera, Tania. Asesor (Managua (Nicaragua), 2000)
Sumario (Es)
Ilus.; 39 ref.
Tesis (Ing. Agr.)
Keywords: BIOGAS; DESINTOXICACION; AGUAS RESIDUALES; PRODUCCION ANIMAL; ESTIERCOL; NICARAGUA; BIODIGESTORES